PENERAPAN METODE BELAJAR PROBLEM SOLVING PADA PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN - Leorince, Leorince; Tirza Cariline Abast; Noviana Shinta Uli; Ninta Tangkelang; Meilia Priskila (Bethel Press, 2021)
Critical thinking skills enable every student to excel in digesting decisions in their daily lives. However, teachers are still not considered to provide space for each student to manage problems into solutions for the future. So the researchers here conducted research on how a teacher becomes a companion in learning through a problem solving method approach. This method of course uses a qualitative with a descriptive approach which is combined to see the depth of the data taken through journals and books. Therefore, it was found from the results of the research that a teacher can implement this problem solving method in learning Christian religious education through the values contained in the Bible, taking a problem that exists in the field, then discussing it to find a solution behind the problem contained in it. field.